Protective effects of atung (Parinarium glaberrimum) seed extract against streptozotocin-induced pancreatic damage: an in vivo experimental study - Manuhutu, Oryza Kenan; Husein, Anggun Lestary; Yuliet Sinanu; Nurul Fadhilah Tamzil; Ayudyaning Pangesti (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2026)
Background: Hyperglycemia, characterized by elevated blood glucose levels, leads to oxidative stress and pancreatic β-cell dysfunction. Streptozotocin (STZ)-induced hyperglycemia in mice is widely used to model pancreatic injury and evaluate antihyperglycemic agents. Atung (Parinarium glaberrimum) seed extract contains antioxidant compounds; however, its effects on pancreatic histopathology remain unclear. Objective: This study aimed to investigate the effect of atung seed extract on pancreatic histopathology in STZ-induced hyperglycemic mice, focusing on islet diameter and histopathological damage. Methods: Twenty-four male Mus musculus (BALB/c) mice were randomly allocated into six groups: normal control, hyperglycemic control, metformin-treated, and three atung seed extract groups (100%, 75%, and 50%). Hyperglycemia was induced using intraperitoneal streptozotocin (40 mg/kgBW). Treatments were administered orally for 21 days. Blood glucose levels were reassessed on day 22 prior to euthanasia. Pancreatic tissues were collected, fixed in 10% neutral buffered formalin, and stained with hematoxylin–eosin. Results: Islet diameter differed significantly among groups (p < 0.05). The ASE75 group showed a mean diameter of 133.01 µm and a median damage score of 1 (IQR 0), comparable to the metformin group (146.61 µm; 0.5 [IQR 1]), whereas the hyperglycemic control group showed severe atrophy (89.02 µm; 3 [IQR 0]). Conclusion: Atung seed extract at a 75% concentration effectively preserved pancreatic β-cell structure, as indicated by increased islet diameter and reduced histopathological damage, supporting its potential as a natural antioxidant-based adjuvant therapy for hyperglycemia management.